O sentido da escola para adolescentes em contexto de vulnerabilidade social - Leite, Fernanda Moreira (2012)
The objective of this dissertation is to analyze the meaning of school for adolescents who live in the context of social vulnerability. For this purpose there are specific objectives: to characterize the bio-socio-demographic information of adolescents and the social vulnerability context in which they live; to analyze the perception of the adolescents related to school activities and the expectations they have about the school. To achieve these objectives, a theoretical referential was used, which is expressed in the following categories: meaning, understood from the cultural-historical theory as a semantic and personal understanding that emerges based on the social context; vulnerability, defined by the integration of three dimensions: individual, social, and programmatic (or institutional); school as human capital, seen as a criticism of the concept of education reduced to the function of generating human skills to work. In regard to the method, a research was conducted in a public school located in an area considered as having social vulnerability in the city of João Pessoa. The area was selected based on the Map of Social Exclusion/Inclusion of the above-mentioned city (Sposati et al.). The study included 12 adolescents aged 13 to 15 years old, attending second level of basic education and who had already failed and been reprimanded by the school´s technical and administrative staff. In addition, a number of students who had neither failed nor been reprimanded were selected, with the purpose of not exposing those who had this history. The sample was defined by Minayo´s saturation criterion. The instruments employed were as follows: 1- mosquito, short questionnaire used to identify the studentes profiles and select those who met the criteria of the study with questions that encompassed age, grade, school performance failure and reprimand by history the school technical and administrative staff; 2 - semi-structured interview, composed of socio-demographic questions and other questions related to the socioeconomic conditions and the level of access to institutional equipment, aimed to characterize the aspect of vulnerability; 3- Sentence Completion Task, addressing questions about life in the neighborhood, in school, and future prospects of the participants. For the data analysis, a descriptive analysis was made in the mosquito questionnaire; for the semi-structured interview, Bardin’s content analysis was used, and for the Sentence Completion Task, the quantitative-interpretative model of Alves was used. The data showed that the vulnerability context of the participants is characterized especially by the lack of structural aspects, exposing the subjects to precarious life conditions. In regard to school, data showed that adolescents recognize it is a place of knowledge and learning that allow prospects for a dignified future based on qualification. Nevertheless, they disagree on how the study is conducted and enforced to them at school and they express that it must be performed by fostering the formation of affective bonds and by creating opportunities for fun and recreation. It is understandable, then, that the meaning that school takes for these adolescents configures it as a privileged space for the cultivation of friendships and fun, without disregarding the importance of formal learning, since it occurs in a context permeated by emotional bonds.